Utilization of Handcrafted Trocar “PP-Ports Trocar” in Laparoscopic Cholecystectomy - Phongmanjit, Phichai (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2024)
Background: Gallstone disease, including symptomatic gallstones, chronic and acute cholecystitis is prevalent worldwide. Laparoscopic cholecystectomy (LC) has emerged as the treatment of choice for these conditions. However, the cost of LC remains a concern due to various factors, including the expenses associated with instrumentation. This study seeks to assess the feasibility, utility and outcomes of laparoscopic cholecystectomy performed with the PP-Ports Trocar, an innovative and cost-effective alternative, compared to conventional commercial trocars. Objective: To evaluate the feasibility and utility of PP-Ports Trocar in laparoscopic cholecystectomy. Method: A retrospective analysis of electronic medical records from September 2023 to February 2024 was conducted. Patients who underwent LC using PP-Ports Trocar were compared with those using commercial trocars at Mae Fah Luang University Medical Center Hospital. Demographic data, surgical time, blood loss, hospital stay, and postoperative complications were analyzed. Results: Twenty patients were included in the study, evenly distributed among two groups based on trocar type. No surgical complications were observed. PP-Ports Trocar demonstrated comparable outcomes to commercial trocars in terms of surgical time, blood loss, hospital stay and postoperative complications. Conclusion: PP-Ports Trocar presents a promising alternative for laparoscopic cholecystectomy, offering cost-effective instrumentation without compromising surgical outcomes. Its adoption could potentially alleviate financial burdens associated with surgical procedures.